Leadership styles in the top greek media companies: leading people with a mixed style - Zotos, Yorgos; Tsourvakas, George; Dekoulou, Paraskevi (My University, 2007)
Media companies are different from manufactures and other commercial organizations. They have both measurable economic goals and nonmeasurable social responsibilities. Leading these companies is a difficult task. The main issue is that an appropriate leadership style for media people must balance business and political goals. In this study, semi-structured interviews were used to collect data about Greek media leaders. The research explores and identifies the leadership style of CEOs heading the top media companies in Greece. These findings indicate that media leaders use a mixed leadership style involving both transformational and transactional styles in order to anticipate the peculiar external and internal media environment.
Keywords: Media companies; Media; Commercial organizations; Media leaders; Greece; Internal media environment